Analyses of Physical and Chemical Compositions of Different Medicinal Specifications of CRPV by Use of Multiple Instrumental Techniques Combined with Multivariate Statistical Analysis - Yang Wang; Weiliang Cui; Guowei Pang; Lewen Xiong; Qingzhi Liu; Lili Xu; Huifen Li; Yongqiang Lin (Molecules, 2022)
Citri Reticulatae Pericarpium Viride (CRPV) is the processed product of Citrus reticulata Blanco. We systematically analyzed two CRPV types, Geqingpi (GQP) and Sihuaqingpi (SHQP), based on powder color, microscopic characteristics, and chemical composition. In addition, we characterized their constituents via ultra-high-performance liquid chromatography with hybrid quadrupole-orbitrap mass spectrometry (UHPLC-Q-Exactive Orbitrap-MS). Both showed significant differences in their powder color and microscopic characteristics. Fourier-transform infrared (FT-IR) spectroscopic analysis results showed that the C=O peak absorption of carboxylic acids and their carbonyl esters in SHQP was higher than that of GQP, while the C-OH and C-H plane bending peaks of polysaccharides were lower than those of GQP. We analyzed these data via similarity analysis, PCA, and OPLS-DA. GQP and SHQP had large distinct differences. Based on the mass measurements for molecular and characteristic fragment ions, we identified 44 main constituents from CRPV, including different flavonoid glycosides and flavonoid aglycones in SHQP and GQP, respectively. We found luteolin-6-C-glucoside, orientin, rhoifolin, and pilloin solely in SHQP, and naringenin and hesperetin only in GQP. The peak area measurements showed GQP having a higher flavonoid glycoside (narirutin, hesperidin, etc.) content, whereas SHQP had a higher polymethoxyflavone (nobiletin, tangeretin, etc.) content. Since we holistically analyzed two CRPV types, the results can not only support future pharmacological research, but also provide a scientific basis for formulating more reasonable CRPV quality standards and guide its clinical potential as a precision medicine.